2017
DOI: 10.1007/978-3-319-40201-7
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Sustainability Strategies in Networks and Clusters

Abstract: of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 105 publications
2
9
0
2
Order By: Relevance
“…Keberlanjutan dalam jaringan ini merupakan konsepsi mereka hingga motivasi dan kondisi yang mendasari untuk sukses. Ini juga mengidentifikasi kebutuhan untuk membangun hubungan antara modal sosial bisnis, daya saing sistem produktif dan kelembagaan untuk menciptakan jaringan berkelanjutan yang "unik" yang membawa karakteristik ekonomi dan budaya dari konteks lokalnya (De Chiara, 2017).…”
Section: Gambar 1 Hasil Pengujian Heteroskedastisitasunclassified
“…Keberlanjutan dalam jaringan ini merupakan konsepsi mereka hingga motivasi dan kondisi yang mendasari untuk sukses. Ini juga mengidentifikasi kebutuhan untuk membangun hubungan antara modal sosial bisnis, daya saing sistem produktif dan kelembagaan untuk menciptakan jaringan berkelanjutan yang "unik" yang membawa karakteristik ekonomi dan budaya dari konteks lokalnya (De Chiara, 2017).…”
Section: Gambar 1 Hasil Pengujian Heteroskedastisitasunclassified
“…Networks, including industrial clusters, are complex adaptive or proactive systems which to a large extent is determined by endogenous and exogenous factors. Therefore, the internationalization behavior and performance of the cluster over time are not a simple sum of the activity of cluster members 6 .…”
Section: Cluster Internationalization Through Network: Theoretical Fmentioning
confidence: 99%
“…Legal recognition of the Solofra tannery district was granted by the regional resolution No.70 on June 2, 1996 but research has shown that a path towards the creation and recognition of the district has not been conclusive (De Chiara, 2016). In actuality, the full operation of the district and a strategic implementation of its committees has never officially been approved; thus, all initiatives conducted by the district and for its development are transferred to public institutions or rely on the commitment of single entrepreneurs who strive to pursue viable actions.…”
Section: The Tannery District Of Soloframentioning
confidence: 99%